2000
DOI: 10.1128/mcb.20.14.5041-5047.2000
|View full text |Cite
|
Sign up to set email alerts
|

AIB1 Is a Conduit for Kinase-Mediated Growth Factor Signaling to the Estrogen Receptor

Abstract: Growth factor modulation of estrogen receptor (ER) activity plays an important role in both normal estrogen physiology and the pathogenesis of breast cancer. Growth factors are known to stimulate the ligand-independent activity of ER through the activation of mitogen-activated protein kinase (MAPK) and the direct phosphorylation of ER. We found that the transcriptional activity of AIB1, a ligand-dependent ER coactivator and a gene amplified preferentially in ER-positive breast cancers, is enhanced by MAPK phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
273
1
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(281 citation statements)
references
References 43 publications
6
273
1
1
Order By: Relevance
“…The relationship between SRC-1 response to the steroid environment and HER2 status is an interesting one, as p160 proteins are known to be phosphorylated via the MAP kinase pathway (Font de Mora and Brown, 2000;Rowan et al, 2000). Taken together, these data provide further evidence of the proposed crosstalk between growth factor receptor pathways and activation of steroid receptor coactivator proteins (Johnston et al, 2003;Osborne et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between SRC-1 response to the steroid environment and HER2 status is an interesting one, as p160 proteins are known to be phosphorylated via the MAP kinase pathway (Font de Mora and Brown, 2000;Rowan et al, 2000). Taken together, these data provide further evidence of the proposed crosstalk between growth factor receptor pathways and activation of steroid receptor coactivator proteins (Johnston et al, 2003;Osborne et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The steroid receptor coactivator (SRC) family of transcriptional coactivators is a target of MAPK phosphorylation. Phosphorylation of SRCs results in an increased ability of these coactivators to recruit additional coregulatory complexes to the DNA-bound receptor [66] [ 67; 68]. It is possible that androgens can induce an autocrine type of feed-forward loop in which androgen-bound AR stimulates the MAPK pathway through direct interaction with cSrc kinase, resulting in phosphorylation of AR and AR coactivators and enhancement of AR transcriptional activity [69; 70; 71].…”
Section: Androgens Activate Second Messenger Pathwaysmentioning
confidence: 99%
“…The gene encoding PPARBP is localized on chromosome 17q12, in close proximity to the HER2/neu amplicon (ERBB2), which is frequently amplified in breast cancer [32]. It is suggested that coactivator upregulation and kinase hyperactivation are part of an integrated mechanism in promoting carcinogenesis [33,34].…”
Section: Estrogen Receptor Cofactors and Breast Cancermentioning
confidence: 99%
“…This action is thought to result after phosphorylation of the ER outside the nucleus i.e., in the cytoplasm or cell membrane, leading to activation of tyrosine kinase receptors such as insulin-like growth factor 1 receptor (IGF-1R), epidermal growth factor receptor (EGFR) and HER2/neu [52]. These receptors then initiate the activation of key downstream signaling kinases such as ERK1,2 mitogen-activated protein kinase (MAPK) and AKT, which in turn phosphorylate and activate the ER and/or its coactivators [34]. This ligand-independent cross talk between the ER and growth factor signaling pathways can sustain activation of pathway signaling and the survival of breast cancer by enhancing the estrogen agonist activity of tamoxifen [53].…”
Section: Endocrine Resistance In Breast Cancermentioning
confidence: 99%